Antagonism between bacillus cereus and pseudomonas fluorescens in planktonic systems and in biofilms - Simões, M. (2008)
In the environment, many microorganisms coexist in communities competing for resources, and they are often associated as biofilms. The investigation of bacterial ecology and interactions may help to improve understanding of the ability of biofilms to persist. In this study, the behaviour of Bacillus cereus and Pseudomonas fluorescens in the planktonic and sessile states was compared. Planktonic tests were performed with single and dual species cultures in growth medium with and without supplemental FeCl3. B. cereus and P. fluorescens single cultures had equivalent growth behaviours. Also, when in co-culture under Fe-supplemented conditions, the bacteria coexisted and showed similar growth profiles. Under Fe limitation, 8 h after co-culture and over time, the number of viable B. cereus cells decreased compared with P. fluorescens. Spores were detected during the course of the experiment, but were not correlated with the decrease in the number of viable cells. This growth inhibitory effect was correlated with the release of metabolite molecules by P. fluorescens through Fe-dependent mechanisms. Biofilm studies were carried out with single and dual species using a continuous flow bioreactor rotating system with stainless steel (SS) substrata. Steadystate biofilms were exposed to a series of increasing shear stress forces. Analysis of the removal of dual species biofilms revealed that the outer layer was colonised mainly by B. cereus. This bacterium was able to grow in the outermost layers of the biofilm due to the inhibitory effect of P. fluorescens being decreased by the exposure of the cells to fresh culture medium. B. cereus also constituted the surface primary coloniser due to its favourable adhesion to SS. P. fluorescens was the main coloniser of the middle layers of the biofilm. Single and dual species biofilm removal data also revealed that B. cereus biofilms had the highest physical stability, followed by P. fluorescens biofilms. This study highlights the inadequacy of planktonic systems to mimic the behaviour of bacteria in biofilms and shows how the culturing system affects the action of antagonist metabolite molecules because dilution and consequent loss of activity occurred in continuously operating systems. Furthermore, the data demonstrate the biocontrol potential of P. fluorescens on the planktonic growth of B. cereus and the ability of the two species to coexist in a stratified biofilm structure.